2021
DOI: 10.3389/fnagi.2021.647875
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in Older Adults and Its Possible Relations With COVID-19

Abstract: Since the beginning of the COVID-19 pandemic, older adults have been found to be a highly vulnerable group, with a higher prevalence of severe cases and negative outcomes. Research has focused on the reasons why older adults are at greater risk; Sleep-related factors have been suggested as one possible explanation for this. An individual’s sleep pattern undergoes significant changes over the course of their life. In older adults a specific sleep profile can be observed, one characterized by advanced sleep timi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 150 publications
2
27
0
1
Order By: Relevance
“…On the other hand, sleep problems (i.e., insufficient sleep duration) may contribute to the manifestation of mood changes through both hypothalamic-pituitaryadrenal (HPA) axis misregulation, and excessive activation of the sympathetic nervous system [19]. In this direction, poor sleep is a common manifestation of both depression and anxiety [20], as they may influence circadian disruption [21]. Not surprisingly, sleep problems are considered symptoms of anxiety and depression [22].…”
Section: Of 17mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, sleep problems (i.e., insufficient sleep duration) may contribute to the manifestation of mood changes through both hypothalamic-pituitaryadrenal (HPA) axis misregulation, and excessive activation of the sympathetic nervous system [19]. In this direction, poor sleep is a common manifestation of both depression and anxiety [20], as they may influence circadian disruption [21]. Not surprisingly, sleep problems are considered symptoms of anxiety and depression [22].…”
Section: Of 17mentioning
confidence: 99%
“…A recent review has focused on the impact of the COVID-19 pandemic by considering sleep disturbances in the older population [21]. The authors found that sleep deprivation and fragmentation, and obstructive sleep apnea may cause a decline of immune responses, leading older individuals to be more likely to contract an infection and, furthermore, a worse prognosis.…”
Section: Of 17mentioning
confidence: 99%
“…The pandemic-related factors, including home confinement, social isolation, and the fear of contracting the virus, could directly impact the sleep of older adults [11]. However, the relationship between sleep and COVID-19 outbreak in the elderly is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from some physical health issues such as weight loss [24,25], the literature has recorded a wide range of psychological feelings, challenges, and concerns reported by people during the pandemic. These psychological feelings and challenges include untold fear and suffering [3], sadness [26], loneliness [6,26], stress [27,28], irritability [29] (Patel, 2021), emotional exhaustion [30], depression [26], sleeping disorders [31], overeating [32], and excessive screen use [33]. Research has also concentrated on various concerns and challenges affecting the whole community in general and older adults, including imposed restrictions [6,26], not being able to go out in public [34], disturbance of social life [27], less physical activities [18], less access to regular medical visits [35], less get-togethers with younger children [34], and loneliness [6,26].…”
Section: Literature Reviewsmentioning
confidence: 99%